2011
DOI: 10.1007/s00299-011-1211-y
|View full text |Cite
|
Sign up to set email alerts
|

Callose deposition at plasmodesmata is a critical factor in restricting the cell-to-cell movement of Soybean mosaic virus

Abstract: Callose is a β-l,3-glucan with diverse roles in the viral pathogenesis of plants. It is widely believed that the deposition of callose and hypersensitive reaction (HR) are critical defence responses of host plants against viral infection. However, the sequence of these two events and their resistance mechanisms are unclear. By exploiting a point inoculation approach combined with aniline blue staining, immuno-electron microscopy and external sphincters staining with tannic acid, we systematically investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
75
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(78 citation statements)
references
References 44 publications
0
75
0
1
Order By: Relevance
“…Callose deposition at the PD is a critical factor in restricting the cell-to-cell viral movement of Soybean mosaic virus (Li et al, 2012). Previous studies of the thermodynamic prediction of the PSTVd structure underscored the importance of some of its RNA motifs such as loops 7 and 8 of the VMR that are critical to both the viroid's replication and its systemic trafficking (Zhong et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Callose deposition at the PD is a critical factor in restricting the cell-to-cell viral movement of Soybean mosaic virus (Li et al, 2012). Previous studies of the thermodynamic prediction of the PSTVd structure underscored the importance of some of its RNA motifs such as loops 7 and 8 of the VMR that are critical to both the viroid's replication and its systemic trafficking (Zhong et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…21 dpi compared with 14 dpi can be attributed to the hypersensitive reaction of the plant's defense system against the invading pathogen (Li et al, 2012). To confirm the decreased expression of the CalS11-like mRNA, we performed RNA gel blot assays using probes specific to the CalS11-like mRNA and to PSTVd.…”
Section: Effect Of the Pstvd Variants On The Cals11-like Mrna Levelsmentioning
confidence: 99%
“…These changes may result from one or more of the following mechanism (s): 1) a direct effect of Hhs.015 inhibition on pathogen growth in the bark lesions, and/or 2) the indirect effect of a Hhs.015-stimulated increase in host resistance to the pathogen. A previous study has demonstrated that callose deposition in plasmodesmata was mainly responsible for restricting the movement of Soybean mosaic virus between plant cells contributing to the defensive response of soybeans to viral infection [14]. …”
Section: Discussionmentioning
confidence: 99%
“…Field trials showed that the recurrence rate of scraped lesions in V . mali - infected apple trees was stably controlled by Hhs.015 with a high level of efficiency (61.29%), which was comparable to common chemical agents such as difenoconazole and tebuconazole [14]. Early studies have shown that Hhs.015 produced heteroauxin, chitinase, proteinase and glucanase.…”
Section: Introductionmentioning
confidence: 99%
“…97 For example, callose deposition may impose a direct physical barrier that restricts intercellular trafficking of the virus through the plasmodesmata. 105 Plant PARPs have also been implicated in differentiation and cell cycle control pathways, 97 which are known to overlap with components of plant signaling in response to stresses. Alterations in the poly(ADP-ribosyl)ation level induced by extrinsic (biotic or environmental) or intrinsic (genetic/physiological) cues play a central role in PARP-mediated cellular stress and developmental signaling processes; 96,97 however the detailed molecular mechanisms underlying the these processes remain largely uncharacterised.…”
mentioning
confidence: 99%